ESTIMATION OF WHITE SHRIMP STOCK (Penaeus mergensis de Man) IN THE WATERS OF THE KAKAP RIVER KUBU RAYA REGENCY, WEST KALIMANTAN - Rajuli, Muhammad .; Soetignya, widadai Padmarsari; Rahayu, Sri (Jurnal Sains Mahasiswa Pertanian, 2019)
ABSTRACT            Information about white shrimp stocks (Penaeus merguensis de Man) is still very minimal, especially in the waters of the Kakap River Kubu Raya Regency, West Kalimantan. This study aims to determine the stock of white shrimp caught in the Kakap River. The method used in sampling is swept area by determining the area of the trawl catching area and taking white shrimp samples 10% of the catch. Research in the field was carried out for 2 months, namely in May-June 2019. Based on the results of research that has been done, the area of trawl fishing gear swept area  reached 0,016 km2. White shrimp caught during the study were 530, of which there were 208 male and 322 females. The long distribution of white shrimp carapace observed during the study ranged from 12,64-41,72 mm, and weighed 1,16-11,45 grams. The length and weight relationship of male, female and combined white shrimp is negative allometric. White shrimp caught  in the Kakap River based on the K value obtained 1,2 results per year with an L∞ value of 21,48 mm male and a K value of 1,2 per year with an L∞ value of 30 mm female, while  the combined obtained a K value of 1,1 per year with L∞ 32,2 mm. Keywords : Relationship of Length and Weight, Growth  dan Carapace Lengh